HOW TO BUILD VOCABULARY IN ENGLISH LEARNERS: STRATEGIES FOR SUCCESS - Sagindikova A.O.; Abduvahabova M.A. (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Annotation: Vocabulary development is fundamental to English language proficiency, directly impacting learners’ reading comprehension, writing abilities, and overall communicative skills. This article outlines effective strategies for building vocabulary among English learners, highlighting the role of direct instruction, context-based learning, and the importance of active practice. Drawing from foundational language acquisition theories and practical classroom methods, this article aims to provide teachers with actionable insights for enhancing students’ vocabulary and improving their linguistic confidence.